"Politics of emotion": Everyday affective circulation of women's resistance and grief in Kashmir. (December 2021) - Kaur, Bhavneet
This article traces women's narratives of the political struggle in Kashmir through the realm of ordinary, scattered, and everyday practices of resistance. It attempts to undo the narrative that overlooks the complexity of women's lives in the face of ongoing violent political conflict; instead it argues that women in Kashmir escape easy categorization into victimhood. This article is embedded in the idea that there is something spectacular in the everydayness of lives embedded in violence; that the everyday is ruptured and layered like the memory of its people. "In Kashmir, which is a historically and politically complex quagmire of violent protests, morbid silence, and killable lives, it is through the barbed spaces of the everyday we see varied surging affects: of loss, of pain, of anger, of endurance, of fear, and of silence" (Kaur). And in this article, I locate women as the protagonists of these circulating affects, inscribing new meanings to the "political" through the politics of emotion.